FOXR1 regulates stress response pathways and is necessary for proper brain development. - Andressa Mota; Hannah K Waxman; Rui Hong; Gavin D Lagani; Sheng-Yong Niu; Féodora L Bertherat; Lynne Wolfe; Christine May Malicdan; Thomas C Markello; David R Adams; William A Gahl; Christine S Cheng; et al. (PLoS Genetics)
The forkhead box (Fox) family of transcription factors are highly conserved and play essential roles in a wide range of cellular and developmental processes. We report an individual with severe neurological symptoms including postnatal microcephaly, progressive brain atrophy and global developmental delay associated with a de novo missense variant (M280L) in the FOXR1 gene. At the protein level, M280L impaired FOXR1 expression and induced a nuclear aggregate phenotype due to protein misfolding and proteolysis. RNAseq and pathway analysis showed that FOXR1 acts as a transcriptional activator and repressor with central roles in heat shock response, chaperone cofactor-dependent protein refolding and cellular response to stress pathways. Indeed, FOXR1 expression is increased in response to cellular stress, a process in which it directly controls HSPA6, HSPA1A and DHRS2 transcripts. The M280L mutant compromises FOXR1's ability to respond to stress, in part due to impaired regulation of downstream target genes that are involved in the stress response pathway. Quantitative PCR of mouse embryo tissues show Foxr1 expression in the embryonic brain. Using CRISPR/Cas9 gene editing, we found that deletion of mouse Foxr1 leads to a severe survival deficit while surviving newborn Foxr1 knockout mice have reduced body weight. Further examination of newborn Foxr1 knockout brains revealed a decrease in cortical thickness and enlarged ventricles compared to littermate wild-type mice, suggesting that loss of Foxr1 leads to atypical brain development. Combined, these results suggest FOXR1 plays a role in cellular stress response pathways and is necessary for normal brain development.